1987
DOI: 10.1073/pnas.84.17.6020
|View full text |Cite
|
Sign up to set email alerts
|

Expression and secretion of type beta transforming growth factor by activated human macrophages.

Abstract: Alveolar macrophages activated with concanavalin A and peripheral blood monocytes activated with lipopolysaccharide secrete type fi transforming growth factor (TGF-j6). There is minimal TGF-/3 secretion in unactivated monocytes, even though TGF-4 mRNA is expressed in these cells at a level similar to that in activated, lipopolysaccharidetreated cultures. U937 lymphoma cells, which have monocytic characteristics, also express mRNA for TGF-j3. Freshly isolated monocytes, both control and lipopolysaccharide-treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
379
0
5

Year Published

1996
1996
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 846 publications
(398 citation statements)
references
References 37 publications
14
379
0
5
Order By: Relevance
“…As shown in Figure 7, these TGF-b-positive cells coincided extremely well with that of antigranulocyte antibody-positive cells, and morphological evidence supported a notion that majorities of these cells were neutrophils (Figure 8). Together with previous reports that TGF-b is distributed in stromal inflammatory cells including granulocytes as well as cancer cells (Roberts et al, 1986;Assoian et al, 1987), it seems reasonable to regard that the predominant source of high levels of TGF-b may be infiltrating neutrophil, though bulk tumoral TGF-b should be accumulation of that from neutrophils, eosinophils and cancer cells. A precise and conclusive cellular source of TGF-b in a tumoral context, however, remains to be identified through in situ hybridisation.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…As shown in Figure 7, these TGF-b-positive cells coincided extremely well with that of antigranulocyte antibody-positive cells, and morphological evidence supported a notion that majorities of these cells were neutrophils (Figure 8). Together with previous reports that TGF-b is distributed in stromal inflammatory cells including granulocytes as well as cancer cells (Roberts et al, 1986;Assoian et al, 1987), it seems reasonable to regard that the predominant source of high levels of TGF-b may be infiltrating neutrophil, though bulk tumoral TGF-b should be accumulation of that from neutrophils, eosinophils and cancer cells. A precise and conclusive cellular source of TGF-b in a tumoral context, however, remains to be identified through in situ hybridisation.…”
Section: Discussionsupporting
confidence: 58%
“…It then remained to determine the identity of the cells that overexpress TGF-b. We initially postulated that these cells were macrophages, since it has been reported that macrophages can secrete TGF-b (Assoian et al, 1987;Appleton et al, 1993) and, moreover, that the expression of TGF-b is associated with fibroblast collagen synthesis (Khalil et al, 1989). However, while the distribution of TGF-b-positive cells and CD68 þ cells was somewhat similar, double-staining IHC did not show consistent double staining with these two antibodies ( Figure 6).…”
Section: Discussionmentioning
confidence: 89%
“…Monocytes/macrophages secrete TGF-β1 which, in turn, regulates numerous responses such as monocyte activation, cytokine production, host defense, and chemotaxis [12,14] . Beyond the accumulating evidence implicating TGF-β1 as a potent immunosuppressive agent [18] , recent studies have highlighted the bidirectional effect of this cytokine on monocyte/macrophage function [11,19] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that lipopolysaccharide (LPS) stimulated human peripheral blood monocytes can induce secretion of TGF-β1 [13] . Further, LPSstimulated murine peritoneal macrophage cells can activate endogenous latent TGF-β1 [14] . These results indicate that LPS-stimulated macrophage cells produce TGF-β1.…”
Section: Introductionmentioning
confidence: 99%
“…8 There is an increasing evidence from several experimental studies that white blood cells, especially monocytes, play a central role in restenosis after balloon angioplasty and stent implantation. [9][10][11][12] Activated monocytes may contribute to neointimal thickening 12 by generating reactive oxygen species through the production of growth and chemotactic factors, 13 binding to a broad repertoire of ligands, 14 or by matrix metalloproteinase production capable of degrading matrix constituents and consequently facilitating cell migration. 15 Monocytes/macrophages have been demonstrated to be one of the components of the neointima.…”
Section: Introductionmentioning
confidence: 99%